2017
DOI: 10.1016/j.seppur.2017.05.043
|View full text |Cite
|
Sign up to set email alerts
|

Nitrite oxidizing bacteria suppression based on in-situ free nitrous acid production at mainstream conditions

Abstract: The application of autotrophic nitrogen removal processes in the main line of wastewater treatment plants will contribute to achieve its self-energy-sufficiency. However, the effective suppression of nitrite oxidizing bacteria (NOB) activity at the conditions of low temperature and low ammonium concentration (mainstream conditions) was identified as one of the main bottlenecks. In this study, stable partial nitritation at 16 ºC and 50 mg NH4 + -N/L was achieved maintaining inside the reactor free nitrous acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
2
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 30 publications
1
21
2
7
Order By: Relevance
“…Indeed, it was proposed that, instead of the low pH value, the actual inhibitor of both bacterial groups, and NOB, is the free nitrous acid (FNA). However, in the present study, due to the observed negligible nitrite accumulation, the maximum FNA concentration reached was of 0.007 mg HNO2-N/L, lower than the reported inhibitory values for AOB and NOB [29]. The sole pH decrease can be responsible for the inhibition of the nitrification process by provoking the deactivation of nitrifying enzymes and changes in the equilibrium carbonate-bicarbonate [28].…”
Section: Reactor Performancecontrasting
confidence: 82%
“…Indeed, it was proposed that, instead of the low pH value, the actual inhibitor of both bacterial groups, and NOB, is the free nitrous acid (FNA). However, in the present study, due to the observed negligible nitrite accumulation, the maximum FNA concentration reached was of 0.007 mg HNO2-N/L, lower than the reported inhibitory values for AOB and NOB [29]. The sole pH decrease can be responsible for the inhibition of the nitrification process by provoking the deactivation of nitrifying enzymes and changes in the equilibrium carbonate-bicarbonate [28].…”
Section: Reactor Performancecontrasting
confidence: 82%
“…Note that a side effect exists of the addition of the coagulant on the alkalinity, with a consumption of 22 mg IC for each 100 mg of FeCl3. 32 Taking into account that the further PN-anammox step requires a minimum alkalinity-to-ammonium ratio of 1-1.25 g IC per g NH4 + -N, 33 the need for an external bicarbonate addition to avoid acidification in the PN-anammox unit, which considers an ammonium concentration of 67 mg NH4 + -N/L (Table 1), would be much higher if the RBF system is not present.…”
Section: Technical Performance Of Combined Rbf and Ces Technologiesmentioning
confidence: 99%
“…Bioaugmentation requires the preexistence of sidestream anammox processes capable of sparing sufficient AOB‐rich sludge to maintain the mainstream dominance of AOB (Cao, van Loosdrecht, & Daigger, 2017; Ma et al, 2016). FNA is more suitable for nitrite‐rich wastewaters such as those in sidestream but not in mainstream applications (Law et al, 2015; Pedrouso et al, 2017). The DO/ammonia ratio control does not suppress K‐strategy NOB for their high affinity to DO (Liu & Yang, 2017); consequently, FA inhibition had to be resorted to (Kowalski, Devlin, di Biase, & Oleszkiewicz, 2019a,2019b).…”
Section: Introductionmentioning
confidence: 99%